Blood pressure and Alzheimer's disease: A review of meta-analysis - Sáiz-Vazquez, Olalla; Puente-Martínez, Alicia; Pacheco-Bonrostro, Joaquín; Ubillos-Landa, Silvia (Frontiers in Neurology, 2023)
Background: AD is a neurological disorder of unknown cause in which the death of brain cells occurs. Identifying some of the modifiable risk factors for AD could be crucial for primary prevention and could lead to reduce the incidence of AD. Objective: We aimed to perform a meta-meta-analysis of studies to assess the effect of blood pressure on diagnosis of AD. Method: The search was restricted to meta-analyses assessing high systolic and diastolic blood pressure and Alzheimer’s disease. We applied the PRISMA guidelines. Results: A total of 214 studies were identified from major databases. Finally, five meta-analyses (52 studies) were analyzed in this review. Results confirm that high SBP is associated with AD. The exploration of parameters (sex, age, study design, region, and BP measurements) shows that only region significantly moderates the relationship between BP and AD. Asian people are those whose SBP levels > 140 mmHg are associated with AD. BP is associated with AD in both people ≤65 and ≥65 and in cross-sectional and longitudinal studies. In the case of DBP, only in women is it associated with a higher risk of AD, particularly when DBP levels > 90. Conclusion: SBP is associated with both cerebrovascular disease and AD. Therefore, future studies should use other uncontrolled factors, such as cardiovascular diseases, diabetes, and stroke to explain the relationship between SBP and AD.